The Reconstruction of Islamic Education in Indonesia Through MaqÄá¹£id SharÄ«â€˜ah of Jaseer Auda - Naupal Naupal (Al-Ulum, 2017)
Islamic education in Indonesia has a long history and started around the 13th century, but it faces many challenges. The first of challenge is the existence of logocentrism and the second of the challenge is the school of centrism (mazdhab-centrism). Logocentrism and school of centrism (mazdhab-centrism) in Islamic education has caused the rise of ghulat community and radicalism in Indonesia. For this reason, Islamic education as an implementation of maqÄá¹£id sharÄ«â€˜ah should be reconstructed. Islamic education systems have to change its strategy and operational method. It has to be open and inclusive to foreign resources of school environment as stated by Auda in maqÄá¹£id sharÄ«â€˜ah. By implementing the thought of Audaâ€™s maqÄá¹£id sharÄ«â€˜ah in the Islamic education in Indonesia, it is expected that the competent, broad-minded, humanistic, tolerant, and democratic Muslim communities can be realized. Besides that, the reconstruction of Islamic education can give information to the society that Islam is not as rigid as radicalism claims, but Islam provides a lot of alternatives in solving the present problems.